High-altitude CO 2 clouds on Mars: OMEGA and HRSC observations - Määttänen, Anni; Montmessin, Franck; Gondet, B.; Hoffmann, H.; Scholten, F.; Hauber, E.; Gonzalez-Galindo, F.; Forget, F.; Bibring, J.-P.; Bertaux, Jean-Loup; Neukum, G. (CCSD, 2009)
International audience The Martian climate hosts a rare phenomenon of condensation of the bulk atmosphere. CO 2 condenses on the polar ice caps, but also forms clouds in the atmosphere. The existence of low-level, convective CO 2 clouds in the polar night was indirectly discovered by MOLA [1,2] and modeled in some studies [3-5]. Recently several satellite instruments [6-9] have observed CO 2 clouds also near the equator, but at high altitudes where the temperatures are low enough for CO 2 condensation. Montmessin et al. [7] identified spectroscopically from MEx/OMEGA observations these high-altitude clouds to be composed of CO2 ice crystals by modeling the CO2 ice spectral signature that was observed in a deep CO 2 gas absorption band at around 4.3 μm. In this work we have used the OMEGA [10] and HRSC [11] observations to map the occurrences of the high-altitude CO 2 clouds and their properties. We have also compared the observations to the predictions of the LMD Mars Global Climate Model (LMD-MGCM) [12] and in particular its improved version that extends to the upper atmosphere [13].